Three-dimensional simulation of granular flow using a mesh-free numerical model - Kheirkhahan, Mehran; Omidvar, Pourya; Nikeghbali, Pooyan; Pasereh, Pouya; Nayyer, Shahab (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2024)
The study and modeling of granular materials using various rheological models are intriguing subjects in numerical simulations and are applicable for predicting and investigating the behavior of different materials, such as sand and granules, in various phenomena like dam breaks or dry landslides. In this paper, we conducted three-dimensional simulations of column collapses with limestone and sand using the μ(I) rheological model within the SPH framework. To assess the performance of the developed code, we compared experimental and numerical values of the free surface of granular particles at different time intervals. The results demonstrated that the numerical modeling error is less than five percent. Additionally, we compared particle dispersion conditions at different time points, indicating the high accuracy of the developed code. Therefore, the code developed for three-dimensional conditions, incorporating the μ(I) rheological model, can be effectively applied to similar phenomena.